EFFECTS ON THE PRACTICE PHYSICAL ACTIVITIES OF THE SELF- CONFIDENCE IN INDIVIDUAL OF ACQUIRED BLINDNESS: A STUDY BASED ON ISNAC - "FLORIVALDO VARGAS" INSTITUTE FOR BLIND PEOPLE IN THE STATE OF MATO GRODDO DO SUL. (Fiep Bulletin - online, 2014)
The World Health Organization estimates that  more than 1,5 millions of people are blind in the world .In Brazil there are more than 825.000 blind people so it represents about 7% of our population. The visual deficiency is characterized by a partial visual loss or total visual loss of the ability to see, it can occur in both eyes, limiting the regular performance of an individual .Questions based on these problems come up and also the intention to study the benefits that physical activities in a blind person's everyday life can cause and their effects related to these people self-confidence. The system consisted of the application , register and description of the results of a questionnaire prepared with objective questions about visual deficiency , autonomy , freedom and the practice of physical activities .ISMAC was chosen because it was possible to keep contact with athletes and common people who go to this place and because it is the place in Campo Grande which ministers visual deficients .The qualitative exploratory research used to collect the data through an interview - questionnaire which was applied individually by the researcher who read each question to each of the people who were interviewed. The most part of the index which was concerned to the cause of the blindness was assigned to accidents adding up to 35,3 % , as well as the cane represented the guidance they use more . Many of the interviewed people stated they practice up to three types of physical activities such as judo and football. As far as the relation between physical activities and self - confidence, we had answers such as the following :' locomotion improvement , depression , aptitude , notion of space '. The practice of physical activities has contributed to the independence of action and locomotion, as well as to the self - confidence and as a result decreasing the depression normally acquired for those who lose their right to see . It was possible to realize that the most part of the visual deficients of the ISMAC practice physical activities and those who do not know exactly the benefits they can get by doing exercises.
Keywords: Visual deficiency; physical activities; self - confidence